Optimisation of the critical medium components for better growth of Picochlorum sp. and the role of stressful environments for higher lipid production. (3rd December 2013) - Dahmen, Ines; Chtourou, Haifa; Jebali, Ahlem; Daassi, Dhouha; Karray, Fatma; Hassairi, Ilem; Sayadi, Sami; Abdelkafi, Slim; Dhouib, Abdelhafidh
Abstract BACKGROUND Coastal countries that suffer from a scarcity of water, such as Tunisia, have to cultivate marine microalgae on non‐arable land in order to produce feedstock and overcome their demands of nutrition and energy. In this framework, a green microalga, CTM 20019, was isolated, identified as Picochlorum sp. and tested for its lipid production. RESULTS The dry weight of Picochlorum sp. is composed of 163 g kg−1 lipids, 225 g kg−1 total sugars, 440 g kg−1 proteins and 112 g kg−1 ash rich in potassium, calcium, iron, magnesium and zinc. Gas chromatography–mass spectrometry analysis showed that the main fatty acids were palmitic acid (29%), linolenic acid (26.5%), linoleic acid (23.5%), hexadecatrienoic acid (11%) and hexadecadienoic acid (8.5%). As it is known that culture conditions greatly influence the composition of microalgae, the experiments were designed to optimise the composition of the medium in order to increase Picochlorum sp. growth from OD680nm = 0.53 to OD680nm = 2.2 and lipid accumulation from 163 g kg−1 to 190 g kg−1. The highest lipid contents of 570 and 585 g kg−1 were achieved under phosphate starvation and sodium carbonate supplementation, respectively. Under these conditions, the fatty acid profile is dominated by mono‐unsaturated and polyunsaturated acids, and is therefore suitable for aqua‐culture feeding. However, under high salinity, growth and lipid synthesis are inhibited, and the fatty acids are saturate, and the product is therefore suitable for biodiesel. CONCLUSION This high lipid content rich in essential fatty acids, omega‐6 and omega‐3, endorses this wild strain of Picochlorum sp. as a promising feedstock for aqua‐culture and human nutrition or for the production of biodiesel. © 2013 Society of Chemical Industry